Can molecular hydrogen supplementation reduce exercise-induced oxidative stress in healthy adults? A systematic review and meta-analysis - Li, Yiting; Bing, Renjie; Liu, Meng; Shang, Zhangyuting; Huang, Yan; Zhou, Kaixiang; Bao, Dapeng; Zhou, Junhong (Frontiers in Nutrition, 2024)
Objective Exercise-induced oxidative stress affects multiple neurophysiological processes, diminishing the exercise performance. Hydrogen (H2) can selectively reduce excessive free radicals, but studies observed its “dual effects” on exercise-induced oxidative stress, that is, increasing or decreasing the oxidative stress. Therefore, we here conducted a systematic review and meta-analysis to quantitatively assess the influence of H2 on exercise-induced oxidative stress in healthy adults. Methods We conducted a systematic review of publications across five databases. The following keywords were used for search strategy: [“hydrogen”[Mesh] or “molecular hydrogen” or “hydrogen rich water” or “hydrogen-rich water” or “hydrogen rich saline”] and [“Oxidative Stress”[Mesh] or “Antioxidative Stress” or “Oxidative Damage” or “Oxidative Injury” or “Oxidative Cleavage”] and [“randomized controlled trial”[Mesh] or “randomized” or “RCT”]. We included trials reporting the effects of H2 on exercise-induced oxidative stress and potential antioxidant capacity post-exercise in healthy adults. Additionally, subgroup analyses were conducted to explore how various elements of the intervention design affected those outcomes. Results Six studies, encompassing seven experiments with a total of 76 participants, were included in our analysis. Among these studies, hydrogen-rich water, hydrogen bathing, and hydrogen-rich gas were three forms used in H2 administration. The H2 was applied in different timing, including before, during, or after exercise only, both before and after exercise, and repeatedly over days. Single-dose, multi-dose within 1 day and/or multiple-dose over days were implemented. It was observed that compared to placebo, the effects of H2 on oxidative stress (diacron-reactive oxygen metabolites, d-ROMs) was not significant (SMD = −0.01, 95%CI-0.42 to 0.39, p = 0.94). However, H2 induced greater improvement in antioxidant potential capacity (Biological Antioxidant Potential, BAP) (SMD = 0.29, 95% CI 0.04 to 0.54, p = 0.03) as compared to placebo. Subgroup analyses revealed that H2 supplementation showed greater improvement (SMD = 0.52, 95%CI 0.16 to 0.87, p = 0.02) in the antioxidant potential capacity of intermittent exercises than continuous exercise. Conclusion H2 supplementation can help enhance antioxidant potential capacity in healthy adults, especially in intermittent exercise, but not directly diminish the levels of exercise-induced oxidative stress. Future studies with more rigorous design are needed to examine and confirm these findings. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=364123, Identifier CRD42022364123.